Síntese e atividades antimicrobiana/antioxidante de 1-(pirazolin-1-il)-2-[(aril/heteroaril)metileno] carboidrazidas trifluormetil substituídas - Cavinatto, Susiane (2010)
This work initially describes the regioselective synthesis of a series of 3-alkyl(aryl/heteroaryl)-5-trifluoromethyl-5-hydroxy-4,5-dihydro-1H-pyrazole-1-carbohydrazides (2) from the monocyclocondensation reaction of 4-alkyl(aryl/heteroaryl)-1,1,1-trifluoro-4-methoxy-3-alken-2-ones (1), where alkyl= Me, aryl= Ph, 4-MePh, 1-Naphthyl, heteroaryl= Fur-2-yl, Thien-2-yl, with carbohydrazide. The resulting pyrazolyl carbohydrazides (2) were obtained in good yields (62 92 %) when the reactions were performed in ethanol as solvent at 25 ° C in reaction times of 18 20 hours in the molar ratio of 1:1. In subsequent reaction step, a novel series of semicarbazones (3) derived from initial pyrazolyl carbohydrazides (2) was obtained from the condensation reaction of 3-alkyl(aryl/heteroaryl)-5-trifluoromethyl-5-hydroxy-4,5-dihydro-1H-pyrazole-1-carbohydrazides (2) with aryl/ heteroaryl substituted aldehydes or acetophenone. The semicarbazones (3) were isolated in yields of 52 97 % when the reaction was conducted in ethanol solvent, at temperature of 60 ° C, in reaction time of 7 hours. Secondly, aiming the synthesis of non symmetrical bis-pyrazoles systems, were performed reactions involving 5-trifluoromethyl-3-phenyl-5-hydroxy-4,5-dihydro-1H-pyrazole-1-carbohydrazide (2b) and 2,4-pentanedione. These reactions led to the isolation of ethyl 5-trifluoromethyl-3-phenyl-5-hydroxy-4,5-dihydro-1H-pyrazole-1-carboxylate (6b) and 3,5-dimethyl-1H-pyrazole (7) simultaneously, ando not to the bis-pyrazole system theoretically predicted. Finally, we have tested a cleavage reaction of the carbonyl compound 1,1 -carbonyl-bis-[3-(4-tolyl)-5-trifluoromethyl-1H-pyrazole] (8c), which was, obtained by the bicyclization reaction of 1,1,1-trifluoro-4-(4-tolyl)-4-methoxy-3-buten-2-one (1c) with 1,3-diaminoguanidine hydrochloride. So, the reaction of 8c with phenylhydrazine and hydroxylamine hydrochloride led to the synthesis of 3-(4-tolyl)-5-(trifluoromethyl)-1H-1-phenyl pyrazole and 5-hydroxy-3-(4-tolyl)-5-(trifluoromethyl)-4,5-dihydroisoxazole, respectively. In addition, the series of 3-alkyl(aryl/heteroaryl)-5-trifluoromethyl-5-hydroxy-4,5-dihydro-1H-pyrazole-1-carbohydrazides (2) and the novel semicarbazones (3) were evaluated for antimicrobial activity and antioxidant potential. As the result, only concentrations greater or equal than 125 μg/mL inhibited the growth of tested bacteria and fungi and, through the test of antioxidant activity, by the DPPH method, qualitatively and quantitatively, it was observed that all substances provided activity as trappers of the stable free radical DPPH. The compounds were characterized by 1H and 13C {1H} NMR Spectroscopy, Gas Chromatography coupled to Mass Spectrometry (GC-MS), Infrared Spectroscopy (IR), X-Ray Diffraction and their purity determined by CHN Elemental Analysis.